ICMI : dinamika politik Islam di Indonesia - Makka, A. Makmur; Mashad, Dhuroruddin (Jakarta : Pustaka Cidesindo, 1997)
On the All-Indonesia Muslim Intellectuals Association and its leader Bacharuddin Jusuf Habibie, State Minister for Research and Technology; Islam and politics, politics and government, Indonesia
Bibliography : p. 147-150 and index
Keywords: Ikatan Cendekiawan Muslim Indonesia; Islam -- Indonesia -- Societies, etc; Intelectuals -- Indonesia -- Societies, etc